Blaming others: stigmas related to COVID-19 pandemic in Indonesia and Malaysia - Sabariah Mohamed Salleh,; Nuurrianti Jalli,; Ika Karlina Idris, (Penerbit Universiti Kebangsaan Malaysia, 2022)
High stigma toward COVID-19 sufferers was observed in Indonesia’s and Malaysia’s social media spheres, especially at the beginning of the pandemic in 2020. This study compared individual and interpersonal stigmas through analysis of online conversations and established government protocols in handling COVID-19 in Malaysia and Indonesia. The critical narrative found was ‘blaming others,’ pointing fingers toward other actors, such as certain ethnic and religious groups, for the continuous spread of the virus. We found that stigmatisation of COVID-19 in Indonesia and Malaysia pointed out jarring concerns, 1) lack of knowledge on COVID-19, 2) the need for effective and efficient dissemination of information to avoid victim blaming, and 3) politicisation of COVID-19 for one’s benefit. In times of public health crises such as COVID-19, governments should not only be responsive in formulating just policies that could help to control the spread of the virus but also mitigate stigmatization towards certain members of society. For Indonesian and Malaysian governments, while there were attempts to address COVID-19 stigma through various online and offline campaigns, observers expressed concern over the lack of recognition of the effects of stigma in COVID-19 official protocols. We discovered that COVID-19 protocols did not provide sufficient information on how to develop a safe environment for COVID-19 sufferers, thus preventing people from getting health treatment and other public services during the pandemic. Also, the protocols were found to have strengthened existing negative stereotypes toward marginalised groups.